Depression among end stage renal disease patients on regular haemodialysis : comparing the haemoglobin, nutritional status, blood pressure control, fluid intake and adequacy of dialysis therapy between the depressed versus the nondepressed patients - Kori, Ahlam Naila (2005)
Background: Depression is the most commonly encountered psychiatric problem in patients with end stage renal disease (ESRD) and has been shown to have a significant impact on the morbidity and mortality of these patients. The prevalence rate of depression in ESRD patients on haemodialysis as quoted by Kimmel et al (1998) was 50%. Unfortunately there was no local data on the prevalence of depression in ESRD patients undergoing haemodialysis; hence this study was conducted to address this issue. The objective of the study was also to compare the differences in parameters such as haemoglobin, nutritional status, blood pressure control and adequacy of dialysis between the depressed versus the non depressed ESRD patients. Methodology: This was a cross sectional study conducted on all ESRD patients undergoing haemodialysis in Hospital University Sains Malaysia (HUSM) and Renal Care dialysis centre. The subjects were interviewed using a validated Malay version of Hospital Anxiety and Depression Scale (HADS) questionnaire asa screening tool for depressive illness. The blood and dialysis parameters such as haemoglobin, serum iron, renal function, serum albumin, interdialytic weight gain and blood pressure were obtained and analyzed. Amount of dialysis delivered was measured by urea kinetic modeling (KtN). Result: The local prevalence of depressive illness among ESRD on regular haemodialysis (using 11 as the cutoff point) obtained from this study was 56.8%. On univariate analysis, this study had shown a significantly lower haemoglobin level (1 0.4 vs 11.5; p < 0.009) and higher systolic blood pressure (149.0 vs 138.6; p< 0.031) among the depressed group as compared to the non depressed group of patients. Univariate analysis had also significantly showed more proportion of female in the depressed group as compared to the non depressed group (32.1% vs 24. 7%; p<0.027) On further analysis with multivariate analysis, the haemoglobin and systolic blood pressure control remain statistically significant with p<0.023 andp<0.008 respectively. Multivariate analysis had also significantly showed more proportion of diabetics had depression as compared to non diabetics with p<0.033. Conclusion: In conclusion, local prevalence of depressive illness amongst end stage renal disease patients on haemodialysis was comparable to previous studies. We also found that depressive state was significantly associated with lower haemoglobin level and higher systolic blood pressure. Diabetes was also shown to become an independent risk factor of developing depression.